Aqueous photodegradation of substituted chlorobenzenes: Kinetics, carbon isotope fractionation, and reaction mechanisms. (15th May 2018) - Passeport, Elodie; Zhang, Ning; Wu, Langping; Herrmann, Hartmut; Sherwood Lollar, Barbara; Richnow, Hans-Hermann
Abstract: Substituted chlorobenzenes are the basic substructure of many surface water contaminants. In this study, the isotope fractionation and reaction mechanisms involved during the aqueous direct and indirect photodegradation of CH3 -, Cl-, and NO2 - substituted chlorobenzenes were investigated in laboratory experiments. Only 4-nitrochlorobenzene showed slow but isotopically fractionating direct photolysis. During indirect photodegradation using UV/H2 O2 -generated OH radicals, the pseudo first-order reaction rate constants increased in the order of the NO2 - < Cl- < CH3 - substituted chlorobenzenes. The most pronounced carbon enrichment factors were observed for nitrochlorobenzenes (up to −4.8 ± 0.5‰), whereas the lowest were for chlorotoluenes (≤−1.0 ± 0.1‰). As the substituents became more electron-withdrawing, the activation energy barrier increased, leading to slower reaction rates, and the transition state changed to a more symmetrical or less reactant-like structure, resulting in larger apparent kinetic isotope effects. The results suggest that the rate-determining step in the reaction with OH radicals was the addition of the electrophile to the benzene ring. Even though further research is needed to quantify isotope fractionation during other transformation processes, these results showed evidence that compound specific isotope analysis can be used as a diagnostic tool for the fate of substituted chlorobenzenes in water. Graphical abstract: Image 1 Highlights: Direct and indirect photodegradation of substituted chlorobenzenes (CB) was studied. Significant carbon isotope fractionation was found for chloro- and nitro-CB. Negligible carbon isotope fractionation was found for methyl-CB. Reaction with OH radicals proceeded via rate-determining OH radical ring addition. CSIA can be used to identify indirect photodegradation of substituted CBs.